Prenatal diagnosis of Neu-Laxova syndrome: a case report - Polat Ibrahim; Gul Ahmet; Aslan Halil; Mutaf Cihan; Agar Mehmet; Ceylan Yavuz (BMC, 2002)
Abstract Background Neu-Laxova syndrome is a rare congenital abnormality involving multiple systems. We report a case of Neu-Laxova syndrome (NLS) diagnosed prenatally by ultrasound examination. Case presentation A 29-year-old gravida 3, para 2 woman was first seen in our antenatal clinic at 38 weeks' pregnancy. Except for the consanguinity and two previous abnormal stillborn babies her medical history was unremarkable. On ultrasound examination microcephaly, flat forehead, micrognathia, intrauterine growth restriction, generalized edema of the skin, hypoplastic chest, excessive soft tissue deposition of hands and feet, joint contractures and a penis without scrotal sacs were detected. She delivered a 2000 g male fetus. He died five minutes after delivery. Postmortem examination confirmed the diagnosis of Neu-Laxova syndrome. Conclusion Because of the autosomal recessive inheritance of Neu-Laxova syndrome genetic counseling and early-serial ultrasound examination should be performed at risk families. Early diagnosis of the disease may offer termination of the pregnancy as an option.